Crystal structure of the ternary semiconductor Cu2In14/3□4/3Se8 determined by X-ray powder diffraction data. Issue 3 (19th September 2018) - Delgado, Gerzon E.; Manfredy, Luigi; López-Rivera, S. A.
Abstract : The crystal structure of the partially ordered vacancy compound Cu2 In14 /3 □4/3 Se8, belonging to the system I3 -III7 -□2 -VI12, was analyzed using X-ray powder diffraction data. Several structural models were derived from the structure of the selenium-rich phase β -Cu0.39 In1.2 Se2 by permuting the cations in the available Wyckoff positions. The refinement of the best model by the Rietveld method in the tetragonal space group P $\overline 4 $ 2 c (No 112), with unit-cell parameters a = 5.7487(3) Å, c = 11.5106(6) Å, V = 380.40(3) Å 3, led to R p = 9.0%, R wp = 9.9%, R exp = 7.2%, S = 1.4 for 134 independent reflections. This model has the following Wyckoff site atomic distribution: Cu in 2 e (0, 0, 0); In in 2 b (½, 0, ¼), 2 d (0, ½, ¼), and 2 f (½, ½, 0);□ in 2 f (½, ½, 0); Se in 8 n ( x, y, z ).